Spol, starost in športna izkušnja pri definiranju športnih skupin - Bosnar, Ksenija (Array, 2006)
The analysis of five clusters of subjects defined by sport preferences in previous research of Prot, Gošnik and Bosnar (2006) did not confirm the hypothesis that clusters were going to reflect factors of sport interests. Instead, the results suggested that gender stereotyping have been involved. Therefore, to establish the meaning of gender, age and sport experience in sport preference cluster formation the discriminant analysis was done. Groups of subjects were defined as five distinct clusters obtained by k-means analysis of sport preference scale results of 1294 elementary school pupils. Discriminant analysis gave two significant functions. First function was defined by gender, and the second was defined by age. Four clusters have marked values on first function and near zero values on second function. Two clusters including subjects who reject "male" sports have high values at the positive "female" side of gender dimension. The cluster including pupils with marked under average interests in "female" sports, and cluster composed of subjects prefering some "male" sports and rejecting all the other sports have high values at the negative "male" side of first discriminant function. The cluster including subjects with above average values of preferences on all sports is positioned at the side of lower grades on second function and near origin of the first function. The results confirm importance of gender in cluster formation.